TINJAUAN KRITIS PERILAKU AROGANSI ANAK PEJABAT NEGARA DALAM RELASIONALITAS AKU DAN LIYAN: Perspektif Etika Armada Riyanto - Ghawa Gaga, David Erichson (Sanjiwani: Jurnal Filsafat, 2023)
The focus of this paper is to discuss the impact of the arrogant behavior of children of state officials on relations with others in the perspective of Armada Riyanto's Philosophy of Ethics. The method used by the author in discussing this theme is a critical analysis of relational ethics based on the concept of I and the Others Relationalism initiated by Armada Riyanto. The main source of this article is the book Relasionalitas which was written by Armada Riyanto himself. The arrogant behavior of the children of state officials resulted in the destruction of good relations with others. Arrogant behavior caused by the perpetrator's arrogance and arrogance causes others to only be considered as a complement in the relationships of everyday human life. So that in everyday relations it is not uncommon for others to be only used as objects of violence or persecution. Violence is always contrary to human nature and certainly injures human dignity itself. Armada Riyanto initiated the relational concept of I and the Other so that the other is not only seen as a "third person" who can be oppressed, but Armada Riyanto wants the dignity of the Other to be truly respected and upheld by every human being. Such a concept creates intimate relationships between human beings so that every human being is able to respect and appreciate others as respecting oneself. So the authors come to the finding that in building relationships with others it is necessary to apply relationships that are intersubjective and based on the spirit of love, in which in these relations equality is emphasized between related subjects and respect for others. Such a concept can also overcome problems related to the arrogance of children of state officials which lead to acts of violence.